AODTU-006 Does a hospital alcohol service have a financial impact by way of reduction in length of stay and reduction in readmissions?. (17th June 2017) - Patel, V; Lyons, K
Abstract : Introduction: The scale of alcohol consumption and harmful alcohol use in Tameside is disproportionally higher, than the national average. Method: The Hospital Alcohol Liaison Service (HALS) supports patients attending the Hospital for urgent and planned care, who are identified as dependent drinkers and those who attend as a direct result of alcohol related harm. We launched therapeutic pathways for acute alcohol withdrawal, Monitor lengths of Hospital stay, Educate all staff in Alcohol related harm, Launch protocols to ensure all patients are screened for alcohol related harm, Seamlessly refer patients to Community treatment providers, ensure access to recovery pathways within the community and Reduce Liver Harm.There was an inconsistent approach to Acute Alcohol management. We identified: variable clinical outcomes, protracted hospital stays and high re-admissions rate.The Team consists of 3 Specialist Nurses, Administrator and Gastroenterologist. The team offers a duty response to all Inpatient and Outpatient departments within the hospital, the service also operates a daily Ambulatory Detoxification clinic. The team identify patients with alcohol related harm, initiating, facilitating and evaluating safe clinical treatment pathways. The service involved all staff groups, through multi-disciplinary education programmes. The Team are responsible for delivering training throughout the Trust-sharing expertise and developing skills throughout the nursing and wider clinical community workforce. The Team coordinate safe clinical pathways - which extend past inpatient stay and involve community referral Results: Quantitative data is collated and analysed on a quarterly basis. These are distributed throughout the Trust with recommendations for future service development. Data is sourced through patient feedback: this data reflects a strong position in respect to patient experience of both the treatment process and person centred clinic. Over 3428 patients, have been assessed, treated to date. 84.2% of patients who engaged in Detoxification via the Ambulatory Detox clinic have remained abstinent for over six months. There is a reduction in 30 day, 60 day readmissions for alcohol related primary diagnosis 38.17% and 38.66% respectively as compared with period before the HALS service.Average Lengths of Stay is reduced from 4.7 days to 1.3 days. Saving of £2.2478, 728 by way of 10 112 bed days saved over 3 years (costed @ £220 a day). This has been sustained a period in excess of 3 years. Conclusion: A HALS service can with education programs and early referal to community services, detox protocols and ambulatory protocols has a large impact on alcohol related harm, reduction in lengths of stay and readmissions Reference: . The Lancet, Vol. 384, No. 9958, p1953–1997. Disclosure of Interest: None Declared